(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2021)
To assess the level of health of the population in the regions of the Kyrgyz Republic, a system of private medical and demographic indicators was proposed and an integral indicator of health was calculated. The calculation results showed that during 2005-2018 among the leaders «with a high level of health» were Batken, Osh and Talas regions. Jalal-Abad region in 2005 was in the group of regions «with a high level of health», by 2018 it switched to an «average level of health», while Osh city - on the contrary, «from an average level of health» to a «high level of health». The outsiders «with a low level of health» were Issyk-Kul, Naryn, Chui regions and Bishkek city.